2015
DOI: 10.1038/bjc.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP-β-activated microRNA-223 promotes tumour growth through targeting RASA1 in human colorectal cancer

Abstract: Background:Evidences have shown that the RAS signalling pathway plays an important role in colorectal cancer (CRC). Moreover, RAS-GTPase-activating proteins (RASGAPs) as RAS signalling terminators are associated with tumourigenicity and tumour progression. In this study, we used bioinformatics analysis to predict and study important miRNAs that could target RAS p21 GTPase-activating protein 1 (RASA1), an important member of RASGAPs.Methods:The levels of RASA1 and miR-223 were analysed by real-time PCR, western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Thus, we hypothesized that RASA1 also participates in the pathogenesis of cardiac fibrosis. Previous studies showed that RASA1 is a target gene of miR-223 [17, 18]; however, whether miR-223 regulates RASA1 in CFs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we hypothesized that RASA1 also participates in the pathogenesis of cardiac fibrosis. Previous studies showed that RASA1 is a target gene of miR-223 [17, 18]; however, whether miR-223 regulates RASA1 in CFs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The cell proliferation assay was performed as previously described44. Briefly, Saos-2 or MNNG/HOS cells with over-expression or knocked down-expression of miR-199a-5p were seeded onto 96-well plates at a density of 6 × 10 3 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described44. Protein extracts of cells and tissues were prepared using RIPA lysis buffer (Sigma-Aldrich), and the total protein content was quantified by the BCA protein assay kit (Thermo Scientific, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Also suggestive is the importance of microRNAs miR‐31 and miR‐223, which seem to share a common stimulatory mechanism in CRC proliferation. In this context, C/EBP‐β becomes important as a positive effector of miR‐223 expression . Thus, the attenuating effect of melatonin on the C/EBP‐β cascade would decrease miR‐223 expression, leading finally to prevent the progression of CRC.…”
Section: Multimodal Approach Using Melatonin Against Progression and mentioning
confidence: 99%
“…On the one hand, C/EBP‐β has been found strongly upregulated in CRC, and CRC cells showed reduced invasiveness and malignant potential when transplanted into C/EBP‐β deficient animals . Also suggestive is the importance of microRNAs miR‐31 and miR‐223, which seem to share a common stimulatory mechanism in CRC proliferation. In this context, C/EBP‐β becomes important as a positive effector of miR‐223 expression .…”
Section: Multimodal Approach Using Melatonin Against Progression and mentioning
confidence: 99%